2012
DOI: 10.1371/journal.ppat.1002602
|View full text |Cite|
|
Sign up to set email alerts
|

Peptidoglycan-Modifying Enzyme Pgp1 Is Required for Helical Cell Shape and Pathogenicity Traits in Campylobacter jejuni

Abstract: The impact of bacterial morphology on virulence and transmission attributes of pathogens is poorly understood. The prevalent enteric pathogen Campylobacter jejuni displays a helical shape postulated as important for colonization and host interactions. However, this had not previously been demonstrated experimentally. C. jejuni is thus a good organism for exploring the role of factors modulating helical morphology on pathogenesis. We identified an uncharacterized ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
233
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(240 citation statements)
references
References 77 publications
5
233
1
1
Order By: Relevance
“…Deletion of H. pylori csd4 led to the loss of helical shape, resulting in slightly curved or straight rods that were impaired in murine stomach colonization assays (8). A similar study in C. jejuni, a closely related human diarrheal pathogen, revealed that deletion of the csd4 homolog, pgp1, led to a similar straight rod phenotype with impaired chick colonization ability, a model representing the natural reservoir of this pathogen (9). HPLC analysis of H. pylori ⌬csd4 PG sacculi or purified disaccharide-linked tripeptide digested with Csd4 demonstrated production of a disaccharide dipeptide (i.e.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Deletion of H. pylori csd4 led to the loss of helical shape, resulting in slightly curved or straight rods that were impaired in murine stomach colonization assays (8). A similar study in C. jejuni, a closely related human diarrheal pathogen, revealed that deletion of the csd4 homolog, pgp1, led to a similar straight rod phenotype with impaired chick colonization ability, a model representing the natural reservoir of this pathogen (9). HPLC analysis of H. pylori ⌬csd4 PG sacculi or purified disaccharide-linked tripeptide digested with Csd4 demonstrated production of a disaccharide dipeptide (i.e.…”
mentioning
confidence: 86%
“…9 and 10). Homologs were identified primarily within the ␦ and ⑀ Proteobacteria, Deferribacteres, and Aquificae (9). Although primarily found in helical or curved rodshaped organisms, homologs of Csd4 were identified in a number of rod-shaped bacteria, including ones isolated from deep sea hydrothermal vents and coastal sediments.…”
Section: Csd4 As An Archetype For a New Family Ofmentioning
confidence: 99%
“…For example, Campylobacter jejuni expresses Pgp1, a homolog of Csd4 in H. pylori. 57 Like csd4, deletion of pgp1 results in a straight, rod-shaped cell with defects in motility and colonization of the gastric epithelium. Enzymatically, Pgp1 possesses activity identical to that of Csd4, trimming PG tripeptides to dipeptides (Fig.…”
Section: Peptidoglycanmentioning
confidence: 99%
“…5C). 57 Clearly, remodeling of the PG layer on both large and small scales majorly impacts cell shape and allows the helical bacteria to adopt their characteristic shape.…”
Section: Peptidoglycanmentioning
confidence: 99%
“…Os determinantes genéticos da formação de biofilmes diferem entre as espécies, e pouco se sabe como as estirpes de uma mesma espécie conseguem características genéticas próprias na presença de diferentes origens genéticas (FRIRDICH et al, 2012;SULAEMAN et al, 2012).…”
Section: Biofilmesunclassified